Bispecific NKG2D-CD3 and NKG2D-CD16 Fusion Proteins as Novel Treatment Option in Advanced Soft Tissue Sarcomas - Hagelstein, Ilona; Lutz, Martina S.; Schmidt, Moritz; Heitmann, Jonas S.; Malenke, Elke; Zhou, Yanjun; Clar, Kim L.; Kopp, Hans-Georg; Jung, Gundram; Salih, Helmut R.; Märklin, Melanie; Hinterleitner, Clemens (Frontiers in Immunology, 2021)
Soft tissue sarcoma (STS) constitutes a rare group of heterogeneous malignancies. Effective treatment options for most subtypes of STS are still limited. As a result, especially in metastatic disease, prognosis is still dismal. The ligands for the activating immunoreceptor NKG2D (NKG2DL) are commonly expressed in STS, but generally absent in healthy tissues. This provides the rationale for utilization of NKG2DL as targets for immunotherapeutic approaches. We here report on the preclinical characterization of bispecific fusion proteins (BFP) consisting of the extracellular domain of the NKG2D receptor fused to Fab-fragments directed against CD3 (NKG2D-CD3) or CD16 (NKG2D-CD16) for treatment of STS. After characterization of NKG2DL expression patterns on various STS cell lines, we demonstrated that both NKG2D-CD16 and NKG2D-CD3 induce profound T and NK cell reactivity as revealed by analysis of activation, degranulation and secretion of IFNγ as well as granule associated proteins, resulting in potent target cell lysis. In addition, the stimulatory capacity of the constructs to induce T and NK cell activation was analyzed in heavily pretreated STS patients and found to be comparable to healthy donors. Our results emphasize the potential of NKG2D-CD3 and NKG2D-CD16 BFP to target STS even in an advanced disease.